Celastrol induces ferroptosis in activated HSCs to ameliorate hepatic fibrosis via targeting peroxiredoxins and HO-1 - Piao Luo; Dandan Liu; Qian Zhang; Fan Yang; Yin-Kwan Wong; Fei Xia; Junzhe Zhang; Jiayun Chen; Ya Tian; Chuanbin Yang; Lingyun Dai; Han-Ming Shen; et al. (Elsevier, 2022)
Ferroptosis is a form of regulated cell death, characterized by excessive membrane lipid peroxidation in an iron- and ROS-dependent manner. Celastrol, a natural bioactive triterpenoid extracted from Tripterygium wilfordii, shows effective anti-fibrotic and anti-inflammatory activities in multiple hepatic diseases. However, the exact molecular mechanisms of action and the direct protein targets of celastrol in the treatment of liver fibrosis remain largely elusive. Here, we discover that celastrol exerts anti-fibrotic effects via promoting the production of reactive oxygen species (ROS) and inducing ferroptosis in activated hepatic stellate cells (HSCs). By using activity-based protein profiling (ABPP) in combination with bio-orthogonal click chemistry reaction and cellular thermal shift assay (CETSA), we show that celastrol directly binds to peroxiredoxins (PRDXs), including PRDX1, PRDX2, PRDX4 and PRDX6, through the active cysteine sites, and inhibits their anti-oxidant activities. Celastrol also targets to heme oxygenase 1 (HO-1) and upregulates its expression in activated-HSCs. Knockdown of PRDX1, PRDX2, PRDX4, PRDX6 or HO-1 in HSCs, to varying extent, elevated cellular ROS levels and induced ferroptosis. Taken together, our findings reveal the direct protein targets and molecular mechanisms via which celastrol ameliorates hepatic fibrosis, thus supporting the further development of celastrol as a promising therapeutic agent for liver fibrosis.